Acute myocardial infarction in a patient with sickle cell trait - Oğuz Akkuş; Mustafa Topuz; Ali Deniz (KARE Publishing, 2016)
Presently described is the rare complication of sickle cell trait (HbAS) with acute inferior myocardial infarction in a young adult patient. Angiogram revealed microemboli in the distal thin segment of the circumflex (Cx) artery. Anticoagulant and anti-aggregant therapies were initiated to restore Cx artery flow. HbAS was detected as an underlying pathology. ST segments returned to the isoelectric line and the patient became asymptomatic.